2015
DOI: 10.1002/app5.78
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Entry into Supply Chain Trade: An Analysis of Firms inSoutheastAsia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 30 publications
4
18
1
Order By: Relevance
“…Xijt refers to a set of variables controlling for enterprise heterogeneity. Following studies by Clarke (2008), Wignaraja (2015), WTO (2018), Banga (2019) and Urata and Baek (2020), in Equation , we capture different aspects of SMEs' characteristics including size, years of operation, formality status, owner/manager's formal education level, trained professional labour and financial assets. As discussed in Section 2.2, these internal factors would have effects on the integration of SMEs into GVCs.…”
Section: Estimation Strategy and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Xijt refers to a set of variables controlling for enterprise heterogeneity. Following studies by Clarke (2008), Wignaraja (2015), WTO (2018), Banga (2019) and Urata and Baek (2020), in Equation , we capture different aspects of SMEs' characteristics including size, years of operation, formality status, owner/manager's formal education level, trained professional labour and financial assets. As discussed in Section 2.2, these internal factors would have effects on the integration of SMEs into GVCs.…”
Section: Estimation Strategy and Datamentioning
confidence: 99%
“…A growing body of literature shows that, depending on a variety of factors, firms take advantage of IT to integrate into GVCs (Elms & Low, 2013;Vo et al, 2010). Internal factors including firm size, age, technological level and ownership are among the determinants of the capacity of firms to adopt IT to join GVCs (Clarke, 2008;Lanz et al, 2018;Wignaraja, 2012Wignaraja, , 2015. External factors such as financial support and information provided by the government, training programmes, legal services, transparent and simplified administrative procedures combine to facilitate firms' IT adoption to integrate into GVCs (Hong et al, 2020;Kowalski et al, 2015;Wignaraja, 2012) and upgrade in GVCs (Banga, 2019;ITC, 2018).…”
mentioning
confidence: 99%
“…Building on the aforementioned study, Wignarajan (2015) included large firms (along with SMEs) and additional variables like human capital to analyse their impact on a firm’s participation in supply chains in Southeast Asian economies. He found that the size of the firm affected economies of scale, which, in turn, determined the firm’s ability to overcome entry costs.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…SMEs contribute significantly towards the development of a country (Cernat et al , 2014; Kalinic and Clegg, 2017); however, they have limited knowledge of internationalization business processes, and thus internationalization can be significantly impeded (Oehme and Bort, 2015; Cahen et al , 2016; Cardoza et al , 2016; Boermans and Roelfsema, 2013). However, on the other hand, it is seen that certain SMEs are internationalizing early (Oehme and Bort, 2015), and researchers are examining these tendencies (Osei-Bonsu, 2014; García-Cabrera et al , 2017; Pickernell et al , 2016) and market entry modes (Keupp and Gassmann, 2009; Singh et al , 2013; Nair and Chelliah, 2012; Wignaraja, 2015; Hennart, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%